Edukasi Kesehatan Gigi dan Pencegahan Kecacingan bagi Anak Usia Dini - Sepriana Urianti; Aryudhi Armis (CV. CENDIKIA JENIUS INDONESIA, 2025)
Dental and helminth infections remain common health problems among early childhood, mainly due to limited knowledge of Clean and Healthy Living Behavior (CHLB). Kindergarten-aged children are vulnerable to dental caries and worm infections caused by poor hygiene habits and lack of education. This activity aimed to increase the understanding of TK Al Kautsar students in Bandar Lampung regarding the importance of maintaining oral hygiene and preventing helminth infections. The methods included health education, toothbrushing demonstrations using a phantom model, group toothbrushing activities, and dental check-ups. The results showed high enthusiasm from students and teachers. Approximately 70% of the children were found to have dental caries, indicating the urgency of early intervention. The activity ran smoothly due to effective collaboration between the community service team and the school. In conclusion, this program effectively improved children’s awareness of dental health and worm infection prevention, and it is recommended for regular implementation and replication in other schools.